What do Cochrane systematic reviews say about telemedicine for healthcare? - Flumignan, Carolina Dutra Queiroz; Rocha, Aline Pereira da; Pinto, Ana Carolina Pereira Nunes; Milby, Keilla Machado Martins; Batista, Mayara Rodrigues; Atallah, Álvaro Nagib; Saconato, Humberto (São Paulo Medical Journal, 2019)
BACKGROUND: Telemedicine has emerged as a tool for overcoming the challenges of healthcare systems and is likely to become increasingly viable, since information and communication technologies have be-come more sophisticated and user-friendly. OBJECTIVE: We aimed to identify all Cochrane systematic reviews (CSRs) on telemedicine within health-care and to summarize the current evidence regarding its use. DESIGN AND SETTING: Review of CSRs, developed at the Discipline of Emergency and Evidence-Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo. METHODS: We searched for studies that compared use of telemedicine with conventional treatment or management of diseases within healthcare. Diagnostic telemedicine studies or studies using automatic text, voice-text or even self-managed care were excluded. The main characteristics and the certainty of evidence were synthetized and critically discussed by all authors. RESULTS: We included 10 CSRs that investigated a broad range of diseases. There is still insufficient ev-idence to determine what types of telemedicine interventions are effective, for which patients and in which settings, and whether such interventions can be used as a replacement for the standard treatment. Harm relating to telemedicine technologies needs to be better investigated and addressed. CONCLUSION: Telemedicine might be an excellent way to facilitate access to treatment, monitoring and dissemination of important clinical knowledge. However, given the recognition of systematic reviews as the best evidence resource available for decision-making, further randomized controlled trials with stricter methods are necessary to reduce the uncertainties in evidence-based use of telemedicine.